2016
DOI: 10.2147/dddt.s86317
|View full text |Cite
|
Sign up to set email alerts
|

Selective CDK7 inhibition with BS-181 suppresses cell proliferation and induces cell cycle arrest and apoptosis in gastric cancer

Abstract: Cyclin-dependent kinase (CDK) family members have been considered as attractive therapeutic targets for cancer. In this study, we aim to investigate the anticancer effects of a selective CDK7 inhibitor, BS-181, in gastric cancer (GC) cell line. Human GC cells (BGC823) were cultured with or without BS-181 at different concentrations for 24–72 hours. BS-181 significantly reduced the activity of CDK7 with downregulation of cyclin D1 and XIAP in GC cells. Treatment with BS-181 induced cell cycle arrest and apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 20 publications
1
31
0
Order By: Relevance
“…33 Wang et al explained that CDK7 inhibition hindered cell proliferation and promoted cell apoptotic rate in GC. 34 Coincidently, in the present study, CDK7 was identified as a target of miR-33a-5p. Our studies further showed that CDK7 knockdown attenuated the promotion impacts of anti-miR-33a-5p on GC cell proliferation, metastasis, and the inhibition effect of that on GC cells apoptosis.…”
Section: Discussionsupporting
confidence: 72%
“…33 Wang et al explained that CDK7 inhibition hindered cell proliferation and promoted cell apoptotic rate in GC. 34 Coincidently, in the present study, CDK7 was identified as a target of miR-33a-5p. Our studies further showed that CDK7 knockdown attenuated the promotion impacts of anti-miR-33a-5p on GC cell proliferation, metastasis, and the inhibition effect of that on GC cells apoptosis.…”
Section: Discussionsupporting
confidence: 72%
“…10,18 In summary, our study showed for the first time that THZ1 may exert its anticarcinogenic effect in HCC cells both in vitro and in vivo in HCC mouse model: (a) inhibiting rapid proliferation of HCC cells; (b) promoting the apoptosis of HCC cells. Thus, THZ1 induced apoptosis by the prolonged CDK7 inhibition in HCC cells.…”
Section: Discussionmentioning
confidence: 67%
“…On the other hand, a challenging problem for the development and use of drugs that target nuclear factors is to increase the permeability of these compounds in the nucleus. The treatment with TPL or THZ1 cause an important reduction in transcription in cancer cell lines, showing that an important amount of these molecules permeates the nuclear membrane 4,44,45, however more precise experiments with animal models are needed. In addition, new methods to increase the efficiency to deliver new drugs to the nucleus still have to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Although other TPL targets have been proposed, structural and biochemical data show that it is very specific for XPB, and intriguingly, the treatment of Drosophila imaginal discs with TPL phenocopies the defects observed in different TFIIH mutant subunits in the fly 41-43. RNA-seq and DNA microarray analyses from TPL-treated cancerous cells have shown the down-regulation of nearly all the RNAPII-dependent transcripts 44,45; however, comparative studies at this level between cancer cells and their progenitors are required. TPL is not highly permeable to the cell membrane, and it is hepatotoxic 46.…”
Section: Tfiih As a Target For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation